PERBANDINGAN PENERAPAN METODE FREQUENT PATTERN TREE DENGAN METODE SQL BASED PATTERN MINING PADA SISTEM PENYIMPANAN DAFTAR PESERTA MATA KULIAH FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS TARUMANAGARA - Gabriel Fransisco; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
The system created to compare the most efficient method among Frequent Pattern Tree method, SQL Based Pattern Mining method and conventional data storage for storing List of Participants Course (DPMK) Information Technology Faculty of Tarumanagara University (FTI Untar). Frequent Pattern Tree method is a method that forming a pattern of courses taken by students using a tree structure. Based Pattern Mining SQL method is a method that forming a pattern of courses by combining the data DPMK becomes a itemsets and take advantage of the features found on the Structured Query Language (SQL) to improve its performance. Conventional data storage is storing DPMK without forming a pattern of courses. The results of the three storage methods are used to form Student Attendance List report and Student Study Cards report. The results show SQL-Based Pattern Mining method is the most efficient method when viewed from the data needed to store and the length of upload time compared to Frequent Pattern Tree method and conventional data storage. However the data call duration used in forming Student Attendance List report and Student Study Cards report using conventional data storage method are  faster than method that use a pattern of courses. Key wordsDafta Peserta Mata Kuliah, Frequent Itemset, Frequent Pattern Mining, Frequent Pattern Tree, SQL Based Pattern Mining